Ingredients of the Whole: Intuition, Environment, and Development - Neal Rassman (Oz, 1985)
Despite Noah Webster's best efforts, design and process are difficult words to define. Individually they resist our efforts to pin them down neatly as if they were the wings of an exotic insect on display…